Comparative Evaluation of Haemagglutination Inhibition Test and Enzyme-linked Immunosorbent Assay for Detection of Antibodies Against Newcastle Disease Vaccine in Broiler Chicks - Tabidi, M.H.; Makkawi, A.; Ali, A.S. (International Journal of Poultry Science, 2004)
The antibody (Ab) titres to the intermediate Newcastle disease virus (NDV) vaccine (Komorov strain) in broiler chicks using haemagglutination inhibition (HI) test and an indirect enzyme-linked immunosorbent assay (ELISA) were compared in this study. The tirtres were compared following vaccination of chicks via the aerosol, intranasal and drinking water routes. For all routes of the vaccine administration, higher Ab tritres were detected using ELISA technique than HI test. For both serological assays, the highest Ab titres detected when the vaccine was administered via the aerosol route with significant level (p< 0.05) compared to the control group. Non-consistent pattern in the Ab levels between the two tests was observed for intranasal and drinking water routes. As a conclusion, ELISA proved more accurate, sensitive and rapid but less economic than HI test when used for detection of Ab titres against NDV vaccines.